Stability and performance of in-situ formed phosphosilicate nanoparticles in phosphoric acid-doped polybenzimidazole composite membrane fuel cells at elevated temperatures - Wang, Zehua; Zhang, J.; Lu, S.; Xiang, Y.; Shao, Zongping; Jiang, San Ping (2024)
One of the effective strategies to pursue the highly durable high-temperature polymer electrolyte membrane fuel cells (HT-PEMFCs) is to introduce inorganic fillers to the phosphoric acid-doped polybenzimidazole (PA/PBI) membranes. Among the inorganic fillers, phosphates such as phosphosilicate are effective in mitigating acid loss at elevated temperatures (200–300 °C). In this paper, the effect of in situ formed phosphosilicate on the performance and stability of SiO2/PA/PBI composite membranes is studied in detail. The mechanical properties and electrochemical performances of the in situ formed SiO2/PA/PBI membranes depend strongly on the content of in situ formed Si5P6O25 fillers and its distribution and microstructure in the membrane. Such in situ formed SiO2/PA/PBI composite membranes show a high conductivity of 53.5 mS cm−1 at 220 °C. The assembled single cell shows a maximum peak power density (PPD) of 530.6 mW cm−2 and excellent stability at elevated temperature of 220 °C for over 130 h. The exceptional stability at 220 °C is most likely due to the existence of predominant amorphous phosphosilicate phases in the in situ formed SiO2/PA/PBI composite membranes, which inhibits the evaporation and leaching of PA at elevated temperatures. The results indicate the practical application of in situ formed SiO2/PA/PBI composite membranes for HT-PEMFCs.